Abnormal Integrity of White Matter Tracts in Acute Lacunar Stroke Patients. Issue 1 (5th September 2018) - Zhu, Yifei; He, Yana; von Deneen, Karen M.; Zhang, Ming
Abstract : Background/Study Concept: Acute lacunar stroke (Als) plays a role in death/disability worldwide. Aphasia refers to chronic difficulty with communication in >20% of patients post stroke. We describe pathophysiological features of white matter (WM) abnormalities and their relationship between WM changes and aphasia quotient (AQ) scores in Als. Methods: Diffusion tensor imaging data were acquired in 37 Als patients and 28 healthy controls. Tract-based spatial statistics (TBSS) and correlation analyses were used. Results: Consistent with the hypothesis, Als had decreased fractional anisotropy (FA) and increased mean diffusivity, axial diffusivity and radial diffusivity in the genu, body and splenium of the corpus callosum (CC), superior longitudinal fasciculus (SLF) and corona radiata in the bilateral hemisphere. Reduced FA of SLF was correlated with AQ scores in Als patients. Conclusion: It is hoped that TBSS could shed new insights into aphasia mechanisms in Als to help promote aging-related disease studies.